1980
DOI: 10.1161/01.str.11.5.494
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral blood flow and edema following carotid occlusion in the gerbil.

Abstract: SUMMARY A technique for measuring focal cerebral blood flow (CBF) and brain specific gravity (SG) in gerbils is described; CO S reactivity and autoregulation were tested. The mean CBF was 29.5 ± 4.5 ml/100 gm/min and brain SG 1.0500 ±0.0004. Unilateral carotid occlusion resulted in a reduction of flow to 12.8 ± 5.8 ml/100 gm/min in the ipsilateral hemisphere with little change in the contralaterai hemisphere; there was also a decrease in brain SG. One hour after occlusion, brain edema, as judged by decreased S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0
3

Year Published

1982
1982
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(54 citation statements)
references
References 36 publications
1
50
0
3
Order By: Relevance
“…In the work of Crockard et al (1980) (as in ours) the animals were sacrificed exactly 1 h after carotid occlusion, which, they showed, resulted in a reduc tion of flow of 12.8 ± 5.8 ml/100 gpm (that is a reduction of 43%; P < 0.001) on the ipsilateral side, the reduction in flow persisting throughout the hour. In the contralateral hemisphere, on the other hand, there was a wide variety of results, some times a marked reduction, at others little change or an increase.…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…In the work of Crockard et al (1980) (as in ours) the animals were sacrificed exactly 1 h after carotid occlusion, which, they showed, resulted in a reduc tion of flow of 12.8 ± 5.8 ml/100 gpm (that is a reduction of 43%; P < 0.001) on the ipsilateral side, the reduction in flow persisting throughout the hour. In the contralateral hemisphere, on the other hand, there was a wide variety of results, some times a marked reduction, at others little change or an increase.…”
Section: Resultsmentioning
confidence: 58%
“…The column having been calibrated with liquids of known specific gravity at the beginning of the ex periment, and cross-calibrated against the column used by Crockard et al (1980), the small pieces of grey matter were dropped into the fluid column and their position noted 3 min after insertion. There was only a small variation in the specific gravity of sam ples taken from a particular area.…”
Section: Methodsmentioning
confidence: 99%
“…There were no significant differences between MK-801 -and placebo-treated groups (0 = normal, 1 2 = most severe damage). The most striking factor these studies have in common, besides the obvious decreases in neuronal damage, is that all employed some form of focal or forebrain ischemia (i.e., incomplete cerebral isch- (Levy and Brierley, 1974;Osburne and Halsey, 1975;Crockard et al, 1980;Suzuki et al, 1983). In the rat model of forebrain ischemia, as employed by Church et al (1988) and Park et al (1988a), Kagstrom et al (1983) shown to decrease to 25% of preischemic values within 4 min (Michenfelder and Theye, 1970).…”
Section: Figmentioning
confidence: 99%
“…Using the gerbil, which has an incomplete circle of Willis, it is possible to produce unilateral ischaemia of varying severity, with little or no change in the contralateral hemisphere (Crockard et al, 1980). Bilateral carotid occlusion produces profound homogeneous hemispheric cortical isch-aemia (Avery et aI., 1984).…”
mentioning
confidence: 99%